(untitled) (Latakia University Journal -Basic Sciences Series, 2022)
The Syrian coast is characterized by the abundance of water resources and the multiplicity of agricultural activities, and the consequent excessive use of organic pesticides, which play a major role in marine water pollution. The Ross River and the area opposite the estuary of the Pine River. Qualitative and quantitative analysis of the final extracts of the studied samples was carried out using gas chromatography/ mass spectrometry (GC/MAS) technology using a GC device. The results showed that the regions of Jableh port and an area opposite the mouth of the Pine River are the most studied areas prevalent for these pollutants, which indicates that This area was affected by the agricultural and sewage drainage canals that flow directly into it, in addition to the agricultural activity in the surrounding areas. The concentrations of substances in the winter season were higher than in the summer, and the compounds Naled, Movinophose and Malathion were the most abundant in these areas. The compound Movinophose had the highest concentration in the pine region, where its concentration reached 4.8 g/lµ, while the compound Naled 1.22 g/lµ had the highest concentration in the Ross River region, and the compound Malathion had the highest concentration in this area of ​​the port of Jableh, where its concentration reached g/lµ 1.5, the results showed that the areas of Jableh port and the area opposite the mouth of the Pinaw River are the most studied areas that spread these pollutants, which indicates that this area is affected by the sewage and agricultural channels that flow directly into it, in addition to the agricultural activity in the surrounding areas, while the area opposite the mouth of the Ross River It is the least studied area that spreads these pollutants, especially in the summer, and the concentrations of pollutants were below the detection limits, which indicates a decline in agricultural activity in the surrounding areas.